Physical education and quarantine - Józef Węglarz (University of Applied Sciences in Tarnow, Poland, 2020)
Scientific knowledge, supported by research intuition, is able to predict a lot but not everything. A worldwide epidemic has not been foreseen, and therefore it caused massive havoc and disturbance in the functioning of all areas of life. This affected education in a great degree, and physical education in particular, because it was unable to use its basic element - motion. This difficult period for physical education should be an opportunity for revising the views on the contents of the curriculum and to change the emphasis on the process of education and physical education respectively. Education should regain priority.